High-release anion synthetic leather and preparation method thereof
By adding negative ion release powder and conductive powder to different levels of synthetic leather, and adjusting the content and hierarchy, the problem of low negative ion release efficiency in the prior art is solved, and a more efficient air purification effect is achieved.
Patent Information
- Application Number
- CN202411809435.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The existing negative ion synthetic leather has the problem of low negative ion release efficiency in structure and process, which makes it difficult for internal negative ions to be released outward, reducing the air purification effect.
The design of high-release negative ion synthetic leather is adopted, in which negative ion release powder and conductive powder are added to the base cloth layer, bonding layer and topcoat layer. By adjusting the powder content and hierarchy, a significant concentration gradient and resistance gradient are formed to promote the outward release of negative ions.
It significantly improves the release amount and efficiency of negative ions, enhances the air purification capacity, and improves the air quality in the car.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of synthetic leather and relates to a high-release anion synthetic leather and a preparation method thereof. Background Art
[0002] With the improvement of living standards, cars have gradually become popular in every household. However, as an essential tool for daily travel, the air environment inside cars is really worrying. According to the indoor air quality standard, nearly 90% of the air inside cars contains formaldehyde or benzene, etc., which exceeds the standard, and the exceeding standard is more serious in new cars. These toxic substances not only chronically harm our health, but also indirectly lead to safety accidents. Studies have found that negative ions in the air can absorb and settle toxic substances and suspended particles of pollutants in the air, purify the air, and improve the indoor air quality of cars. Therefore, automotive interior materials with negative ion release function are becoming more and more popular.
[0003] In the prior art, relevant personnel have conducted a certain degree of research on negative ion functional materials. For example, patent CN108049032A discloses a method for preparing a non-woven fabric with a strong negative ion release function, by blending tourmaline powder with other raw materials in the spinning process, and then melt spinning to finally prepare a non-woven fabric with a strong negative ion release function. However, such non-woven fabrics are very brittle due to the addition of inorganic powders. The main strength contribution of synthetic leather comes from the non-woven fabric fiber skeleton composed of ultra-fiber materials. When non-woven fabrics made of such fibers are used for synthetic leather, the mechanical properties of synthetic leather will be greatly reduced. In addition, after the non-woven fabric is wrapped with polyurethane, it is difficult to release negative ions inside.
[0004] The existing negative ion synthetic leather on the market is usually composed of a base fabric layer, an adhesive layer and a topcoat layer stacked in sequence, wherein the base fabric layer contributes to the basic mechanical properties of the synthetic leather, the adhesive layer contributes to the bonding function of the topcoat layer and the base fabric layer, and the topcoat layer contributes to the surface functionality and appearance function. Most of the negative ion synthetic leathers currently on the market are made by directly adding tourmaline powder to the polyurethane resin of each layer to make a base fabric, and then coating the adhesive layer and the topcoat layer on the surface of the base fabric in sequence, and finally veneer to make synthetic leather. Although this type of negative ion modified synthetic leather has increased the negative ion release function of the material to a certain extent, it has not considered how to more effectively conduct the negative ions released by the tourmaline powder to the air environment. Moreover, compared with non-woven fabrics, synthetic leather has a larger thickness and a dense structure, and is subject to the structural characteristics of synthetic leather. The negative ions present inside are usually difficult to release outward, thereby greatly reducing the negative ion efficacy.
[0005] Therefore, it is of great significance to study a high-release negative ion synthetic leather and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention
[0006] The purpose of the present invention is to solve the problems existing in the prior art and to provide a high-release anion synthetic leather and a preparation method thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A high-release anion synthetic leather comprises a base fabric layer, an adhesive layer and a topcoat layer, wherein the base fabric layer, the adhesive layer and the topcoat layer are all added with anion-releasing powder and conductive powder;
[0009] The content of negative ion releasing powder in the base fabric layer, the bonding layer and the topcoat layer decreases in sequence, and the content of conductive powder increases in sequence.
[0010] For the high-release negative ion synthetic leather as described above, the increasing amplitude is ≥1%, and the decreasing amplitude is ≥1%. The increasing and decreasing amplitudes refer to the variation amplitude of the powder content in two adjacent layers.
[0011] As described above, the content of negative ion releasing powder in the high-release negative ion synthetic leather is more than 15wt% to ensure that the synthetic leather can produce sufficient negative ion release. If the proportion of negative ion releasing powder is too low, the amount of negative ion release will be limited and cannot meet actual needs.
[0012] In the high-release negative ion synthetic leather as described above, the thickness of the base fabric layer is 0.6 to 1.5 mm; the base fabric layer is the thickest unit structure in the synthetic leather, and its release capacity is limited by the thickness of the base fabric layer. When the thickness is less than 0.6 mm, the base fabric layer itself is thin and the release resistance is small, and the improvement effect is not significant. When the thickness is greater than 1.5 mm, the base fabric layer is too thick compared to the total structure, and the internal negative ions are still difficult to improve; the total content of negative ion releasing powder and conductive powder in the base fabric layer is ≤25wt%, otherwise it will lead to insufficient strength of the base fabric; and the content of conductive powder is ≥2wt%, otherwise it will lead to excessive resistance and cannot contribute to the transmission of negative ions.
[0013] As described above, the thickness of the adhesive layer of the high-release anion synthetic leather is 0.05-0.1 mm; the total content of the anion-releasing powder and the conductive powder in the adhesive layer is ≤25wt%, otherwise the adhesiveness of the adhesive layer is poor, which may easily lead to the peeling of the adhesive layer and the base fabric layer.
[0014] As described above, the thickness of the topcoat layer of a high-release negative ion synthetic leather is 0.02 to 0.05 mm; the total content of negative ion releasing powder and conductive powder in the topcoat layer is ≤25wt%, otherwise the viscosity of the topcoat layer is relatively large, and excessive powder is prone to agglomeration, which in turn leads to poor appearance of the topcoat layer. Such appearance defects will cause the entire synthetic leather to be scrapped.
[0015] For the high-release anion synthetic leather as described above, the anion-releasing powder has an anion release concentration of ≥1000ions / cm per second. 3 The negative ion releasing powder can be tourmaline, negative ion powder, negative ion ceramic powder and modified material having the function of releasing negative ions that meet the negative ion release concentration requirement per unit time. The resistivity of the conductive powder is ≤1*10 3 Ω·cm.
[0016] A method for preparing a high-release negative ion synthetic leather as described in any one of the above items comprises the following steps:
[0017] (1) Configuration of polyurethane modified slurry of base fabric layer: The polyurethane modified slurry of base fabric layer is a slurry containing conductive powder, negative ion releasing powder and polyurethane resin;
[0018] (2) Modified adhesive layer slurry configuration: The modified adhesive layer slurry is a slurry containing conductive powder, negative ion releasing powder and polyurethane resin;
[0019] (3) Modified topcoat layer slurry configuration: The modified bonding layer slurry is a slurry containing conductive powder, negative ion releasing powder and polyurethane resin;
[0020] (4) using a base fabric layer polyurethane slurry to impregnate a non-woven fabric to form a base fabric layer;
[0021] (5) coating the modified adhesive layer slurry on the base fabric layer, and forming an adhesive layer of the high-release anion synthetic leather after curing;
[0022] (6) coating a modified topcoat slurry on the adhesive layer, and forming a topcoat layer of a high-release anion synthetic leather after curing.
[0023] The coating and curing processes of the above-mentioned adhesive layer and topcoat layer are common processes for preparing solvent-based polyurethane synthetic leather.
[0024] In the preparation method of a high-release anion synthetic leather as described above, when the polyurethane modified slurry of the base fabric layer, the modified adhesive layer slurry and the modified topcoat layer slurry are configured, the anion-releasing powder and the conductive powder are first mixed with a solvent to form a slurry, and the slurry is then stirred and mixed with a polyurethane resin.
[0025] In the method for preparing a high-release anion synthetic leather as described above, the viscosity of the polyurethane modified slurry of the base fabric layer is 30,000 to 50,000 CPS;
[0026] The viscosity of the modified bonding layer slurry is 70000~90000CPS;
[0027] The viscosity of the modified topcoat layer slurry is 1000-3000 CPS.
[0028] If the mesh number of the negative ion-releasing powder and the conductive powder is too high, the finer the powder, the easier it is to agglomerate the ground slurry, which is not conducive to subsequent impregnation and coating; if the mesh number is too low, there will be processing problems such as uneven impregnation and coating. The selection of fineness is the result of conventional process adjustment. Those skilled in the art can select the appropriate fineness according to the process conditions. Exemplarily, when preparing the polyurethane modified slurry of the base fabric layer, the mesh number of the negative ion-releasing powder selected is 50-200 mesh, and the mesh number of the conductive powder is 50-200 mesh; when preparing the modified bonding layer slurry, the mesh number of the negative ion-releasing powder selected is 50-200 mesh, and the mesh number of the conductive powder is 50-200 mesh; when preparing the modified topcoat layer slurry, the mesh number of the negative ion-releasing powder selected is 200-500 mesh, and the mesh number of the conductive powder is 200-500 mesh.
[0029] If the stirring speed of the mixed resin is too low and the stirring is insufficient, it will affect the performance of the final material and the stability of the functional indicators; if the speed is too high, it is easy to cause safety hazards. At the same time, the temperature generated by high-speed stirring will accelerate the release of negative ions in advance. The stirring speed of the mixed resin is the result of conventional process adjustments. Those skilled in the art can choose an appropriate processing window according to the mixing results and processing safety under this formula. Exemplarily, when preparing the polyurethane modified slurry of the base fabric layer, the stirring frequency is 30 to 50 Hz; when preparing the modified bonding layer slurry, the stirring frequency is 30 to 50 Hz; when preparing the modified topcoat layer slurry, the stirring frequency is 40 to 60 Hz.
[0030] Invention mechanism:
[0031] The mass concentration of the negative ion-releasing powder decreases from the inside to the outside, forming a significant concentration gradient. It is found that the concentration of negative ions from the inside to the outside is different, forming a concentration difference of high inside and low outside; while the mass concentration of the conductive powder increases from the inside to the outside, forming a significant concentration gradient, then the internal resistance of the synthetic leather is high inside and low outside, forming a resistance potential. Ions tend to migrate in the direction of low resistance. Driven by the negative ion concentration difference, negative ions generate a greater driving force to diffuse outward; further, driven by the resistance potential, negative ions use conductive powder as a medium to migrate more smoothly to the leather surface with low resistance, thereby increasing the release of negative ions. As a result, the high-concentration negative ions released inside migrate to the low-concentration area outside and are then released into the air.
[0032] On the contrary, if the content of the negative ion releasing powder is set to increase from the inside to the outside or the content of the conductive powder is set to decrease from the inside to the outside, it will hinder the amount of negative oxygen ions released by the negative ion releasing powder and discharged into the air.
[0033] Beneficial effects:
[0034] (1) The method for preparing a high-release negative ion synthetic leather of the present invention combines negative ion release and ion conduction to increase the efficiency of negative ion conduction into the air environment while ensuring the release of negative ions, thereby improving the overall negative ion release of the synthetic leather.
[0035] (2) The high-release negative ion synthetic leather of the present invention can release more negative ions, purify the air, and is beneficial to human health. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:
[0038] Viscosity: The viscosity of the polyurethane resin was measured using a rotational viscometer (environment: 25°C ± 5°C, relative humidity not greater than 80%, manufacturer: Shanghai Pingxuan Scientific Instrument Co., Ltd., model: NDJ-8S, rotor No. 3).
[0039] Tensile strength: According to GB / T 1040.3 (Type 2 specimen), the tensile strength of the base fabric was measured using a universal testing machine (environment: 25°C ± 5°C, manufacturer: Shanghai Tuofeng Instrument Technology Co., Ltd., model: TFW-69).
[0040] Negative ion release concentration of powder: A solid negative ion tester is used to measure the negative ion release concentration of the powder (environment: 20°C ± 5°C, humidity between 30% RH and 75% RH, and no static interference, manufacturer: Beijing Huayi Tongtai Technology Co., Ltd., model: IT-10).
[0041] Negative ion release concentration of the sample: According to JC / T 2110-2012, the negative ion release concentration of the sample is measured using an ion collector;
[0042] Resistivity: The resistivity of the conductive powder was measured by a four-probe method (environment: 20°C ± 5°C, humidity between 30% RH and 75% RH, and no static interference, manufacturer: Suzhou Jingge Electronics Co., Ltd., model: ST2258C).
[0043] The above performance data of all the embodiments and comparative examples of the present invention are measured under an experimental environment of 23° C. and a relative humidity of 55%.
[0044] Ingredients Description:
[0045] The base fabric of the present invention is a microfiber base fabric or a non-microfiber base fabric. When the base fabric is a microfiber base fabric, the known method is to first prepare the island fiber base fabric by impregnating the island fiber nonwoven fabric with polyurethane slurry, and then open the fiber to prepare the microfiber base fabric.
[0046] The nonwoven fabric used in the present invention is a sea-island fiber nonwoven fabric produced by Jiangsu Huafeng Microfiber Materials Co., Ltd. The sea-island fiber nonwoven fabric has a gram weight of 340 g / m 2 After opening, the weight of the microfiber base fabric and resin is 420g / m 2 .
[0047] The negative ion releasing powder and the conductive powder used in the present invention are as follows:
[0048] Negative ion release powder 1: Tourmaline, the negative ion release concentration per second is 1000ions / cm 3 , mesh number 100;
[0049] Negative ion release powder 2: Tourmaline, the negative ion release concentration per second is 1000ions / cm3, ground to a particle size of 200 mesh;
[0050] Negative ion release powder 3: Tourmaline, the negative ion release concentration per second is 1000ions / cm 3 , grind to particle size 500 mesh.
[0051] Conductive powder 1: conductive carbon black, resistivity is 1000Ω·cm, particle size is 200 mesh;
[0052] Conductive powder 2: conductive carbon black, resistivity 1000Ω·cm, ground to a particle size of 500 mesh;
[0053] Conductive powder 3: graphene, resistivity is 500Ω·cm, particle size is 50 mesh;
[0054] Conductive powder 4: graphene, resistivity 500Ω·cm, ground to a particle size of 200 mesh;
[0055] Conductive powder 5: SnO2, resistivity is 5000Ω·cm, mesh size is 50 mesh.
[0056] The type of polyurethane described in the present invention is solvent-based polyurethane, and the solvent used is conventional DMF.
[0057] Polyurethane resin slurry 1 used for polyurethane modified slurry of base fabric layer: HDD-8060HT brand polyurethane resin slurry purchased from Shanghai Huide Technology Co., Ltd., with a solid content of 29-31%, is mixed with functional powder slurry. The amount of solvent in the functional powder slurry is determined according to the different target viscosity slurries that need to be prepared;
[0058] Polyurethane resin slurry 2 used for modified bonding layer slurry: HDA-4030 polyurethane resin slurry purchased from Shanghai Huide Technology Co., Ltd., with a solid content of 39-41%, is mixed with functional powder slurry. The amount of solvent in the functional powder slurry depends on the different target viscosity slurries that need to be prepared;
[0059] Polyurethane resin slurry 3 used for modified topcoat layer slurry: HDS-3030YB brand polyurethane resin slurry purchased from Shanghai Huide Technology Co., Ltd. is used, with a solid content of 29-31% and mixed with functional powder slurry. The amount of solvent in the functional powder slurry depends on the different target viscosity slurries that need to be formulated.
[0060] When preparing the above-mentioned layers of powder-modified polyurethane resin slurry, the stirring frequency is set to 50 Hz, and the mixing is carried out at this frequency.
[0061] The total solid content of the slurry = (polyurethane resin + negative ion releasing powder + conductive powder) / total weight of the slurry.
[0062] Example 1
[0063] A method for preparing high-release negative ion synthetic leather, the specific steps are as follows:
[0064] (1) Preparation of polyurethane modified slurry for base fabric layer: The conductive powder 3 and the negative ion releasing powder 2 are first mixed with a solvent to form a slurry, and then stirred and mixed with the polyurethane resin slurry 1 to prepare a polyurethane modified slurry for the base fabric layer with a viscosity of 50,000 CPS;
[0065] Among them, the content of the negative ion releasing powder 2 is 7.4wt%, the content of the conductive powder 3 is 1wt%, and the total solid content of the polyurethane modified slurry of the base fabric layer is 32.9wt%;
[0066] (2) Modified adhesive layer slurry preparation: The conductive powder 4 and the negative ion releasing powder 2 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 2 to prepare a modified adhesive layer slurry with a viscosity of 80,000 CPS;
[0067] Among them, the content of the negative ion releasing powder 2 is 5.4wt%, the content of the conductive powder 4 is 1.9wt%, and the total solid content of the modified bonding layer slurry is 43.2wt%;
[0068] (3) Preparation of modified topcoat layer slurry: The conductive powder 4 and the negative ion releasing powder 2 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 3 to prepare a modified topcoat layer slurry with a viscosity of 2000 CPS;
[0069] Among them, the content of the negative ion releasing powder 2 is 2.5wt%, the content of the conductive powder 4 is 1.9wt%, and the total solid content of the modified topcoat layer slurry is 25.3wt%;
[0070] (4) using the polyurethane slurry of the base fabric layer to impregnate the non-woven fabric, and after coagulation and water washing, a sea-island fiber base fabric layer with a thickness of 0.9 mm is prepared, and then after reduction, an ultra-fine fiber base fabric layer is obtained, wherein the content of the negative ion releasing powder 2 in the ultra-fine fiber base fabric layer is 14.8 wt %, and the content of the conductive powder 3 is 2 wt %;
[0071] (5) coating the modified adhesive layer slurry on the microfiber-based fabric layer, and forming an adhesive layer of a high-release anion synthetic leather with a thickness of 0.1 mm after curing, wherein the content of the anion-releasing powder 2 in the adhesive layer is 12.5 wt %, and the content of the conductive powder 4 is 4.4 wt %;
[0072] (6) A modified topcoat slurry is coated on the adhesive layer, and after curing, a topcoat layer of a high-release anion synthetic leather with a thickness of 0.05 mm is formed, wherein the content of the anion-releasing powder 2 in the topcoat layer is 9.9 wt %, and the content of the conductive powder 4 is 7.5 wt %.
[0073] The content of negative ion releasing powder in the finally prepared high-release negative ion synthetic leather is 15wt%, and the negative ion release concentration per second in the high-release negative ion synthetic leather is 1326ions / cm 3 .
[0074] Comparative Example 1
[0075] A method for preparing a releasing negative ion synthetic leather is basically the same as that of Example 1, except that no conductive powder is added to the base fabric layer, the adhesive layer and the topcoat layer.
[0076] The content of negative ion releasing powder in the finally prepared negative ion releasing synthetic leather is 15wt%, and the negative ion release concentration per second is 707ions / cm 3 .
[0077] By comparing Comparative Example 1 with the embodiment, it can be found that the concentration of negative ions released per second by the synthetic leather prepared in Comparative Example 1 is significantly lower than that in Embodiment 1. This is because after the resistance difference of each layer is removed, the driving force for the negative ions to diffuse outward is weakened. It can be seen that negative ions are more inclined to migrate in the direction of low resistance. Driven by the resistance potential, the negative ions use the conductive powder as a medium to migrate more smoothly to the leather surface with low resistance, thereby increasing the release of negative ions.
[0078] Comparative Example 2
[0079] A method for preparing a negative ion releasing synthetic leather is basically the same as that of Example 1, except that the conductive powder 3 in the polyurethane modified slurry of the base fabric layer is replaced with the conductive powder 5.
[0080] The content of negative ion releasing powder in the finally prepared negative ion releasing synthetic leather is 15wt%, and the negative ion release concentration per second is 1001ions / cm 3 .
[0081] By comparing Comparative Example 1 with Example 1, it can be found that the concentration of negative ions released per second by the synthetic leather prepared in Comparative Example 1 is significantly lower. This is because the resistivity of the conductive powder 5 is too large, and it is difficult for negative ions to migrate smoothly to the leather surface with low resistance through the conductive powder 5.
[0082] Comparative Example 3
[0083] A method for preparing a releasing negative ion synthetic leather is basically the same as that in Example 1, except that the concentration of the conductive powder in each layer is adjusted so that the concentration gradient trend of the conductive powder is opposite to that in Example 1. The specific adjustment method is:
[0084] Step (1) The content of the conductive powder 3 in the polyurethane modified slurry of the base fabric layer is 1.4 wt %, and the other components remain unchanged;
[0085] Step (2) The content of the conductive powder 4 in the modified bonding layer slurry is 0.7 wt %, and the other components remain unchanged;
[0086] The content of the conductive powder 4 in the modified topcoat layer slurry of step (3) is 0.1 wt %, and the other components remain unchanged.
[0087] In the final released negative ion synthetic leather, the content of negative ion releasing powder 2 in the base fabric is 14.8wt%, and the content of conductive powder 3 is 2.8wt%; the content of negative ion releasing powder 2 in the adhesive layer is 12.9wt%, and the content of conductive powder 4 is 1.7wt%; the content of negative ion releasing powder 2 in the topcoat layer is 10.6wt%, and the content of conductive powder 4 is 0.4wt%.
[0088] The content of negative ion releasing powder in the negative ion releasing synthetic leather is 15.1wt%, which is basically the same as that in Example 1. The negative ion release concentration per second is 612ions / cm 3 .
[0089] By comparing Comparative Example 3 with Example 1, it can be found that the concentration of negative ions released per second by the synthetic leather prepared in Comparative Example 3 is significantly lower than that in Example 1. This is because after the mass concentration of the conductive powder in Comparative Example 3 decreases from the inside to the outside, it induces the reverse migration force of negative ions from the outside to the inside, which in turn leads to a serious reduction in the amount of negative ion release.
[0090] Comparative Example 4
[0091] A method for preparing a release-type anion synthetic leather is basically the same as in Example 1, except that the concentration of the anion-releasing powder in each layer is adjusted so that the concentration gradient trend of the anion-releasing powder is opposite to that in Example 1. The specific adjustment method is:
[0092] Step (1) The content of the negative ion releasing powder 2 in the polyurethane modified slurry of the base fabric layer is 7 wt %, and the other components remain unchanged;
[0093] Step (2) The content of the negative ion releasing powder 2 in the modified bonding layer slurry is 7 wt %, and the other components remain unchanged;
[0094] Step (3) The content of the negative ion releasing powder 2 in the modified topcoat layer slurry is 4.8 wt %, and the other components remain unchanged;
[0095] In the final released negative ion synthetic leather, the content of negative ion releasing powder 2 in the base fabric is 14wt%, and the content of conductive powder 3 is 2wt%; the content of negative ion releasing powder 2 in the bonding layer is 15.6wt%, and the content of conductive powder 4 is 4.2wt%; the content of negative ion releasing powder 2 in the topcoat layer is 17.4wt%, and the content of conductive powder 4 is 6.9wt%.
[0096] The content of the negative ion releasing powder in the negative ion releasing synthetic leather is 15wt%, which is consistent with Example 1, and the negative ion release concentration per second is 841ions / cm 3 .
[0097] By comparing Comparative Example 4 with the embodiment, it can be found that the concentration of negative ions released per second by the synthetic leather prepared in Comparative Example 4 is significantly lower than that in Embodiment 1. This is because the mass concentration of the negative ion releasing powder in Comparative Example 4 increases from the inside to the outside, causing the trend of the negative ion releasing powder itself to diffuse outward using the concentration difference to become inward diffusion, resulting in a serious reduction in the amount of negative ion release.
[0098] Example 2
[0099] A method for preparing high-release negative ion synthetic leather, the specific steps are as follows:
[0100] (1) Preparation of polyurethane modified slurry for base fabric layer: The conductive powder 3 and the negative ion releasing powder 1 are first mixed with a solvent to form a slurry, and then stirred and mixed with the polyurethane resin slurry 1 to prepare a polyurethane modified slurry for the base fabric layer with a viscosity of 40000 CPS;
[0101] Among them, the content of the negative ion releasing powder 1 is 7.7wt%, the content of the conductive powder 3 is 1.9wt%, and the total solid content of the polyurethane modified slurry of the base fabric layer is 32.3wt%;
[0102] (2) Modified adhesive layer slurry preparation: The conductive powder 3 and the negative ion releasing powder 1 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 2 to prepare a modified adhesive layer slurry with a viscosity of 80,000 CPS;
[0103] Among them, the content of the negative ion releasing powder 1 is 6.3wt%, the content of the conductive powder 3 is 3.7wt%, and the total solid content of the modified bonding layer slurry is 45.3wt%;
[0104] (3) Preparation of modified topcoat layer slurry: The conductive powder 4 and the negative ion releasing powder 3 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 3 to prepare a modified topcoat layer slurry with a viscosity of 1000 CPS;
[0105] Among them, the content of the negative ion releasing powder 3 is 3.1wt%, the content of the conductive powder 4 is 3.2wt%, and the total solid content of the modified topcoat layer slurry is 26.5wt%;
[0106] (4) using the polyurethane slurry of the base fabric layer to impregnate the non-woven fabric, and after coagulation and water washing, a sea-island fiber base fabric layer with a thickness of 1.2 mm is prepared, and then after reduction, an ultra-fine fiber base fabric is obtained, wherein the content of the negative ion releasing powder 1 in the ultra-fine fiber base fabric layer is 16 wt %, and the content of the conductive powder 3 is 3.9 wt %;
[0107] (5) coating a modified adhesive layer slurry on the microfiber-based fabric layer, and curing to form an adhesive layer of a high-release anion synthetic leather with a thickness of 0.05 mm, wherein the content of the anion-releasing powder 1 in the adhesive layer is 13.9 wt %, and the content of the conductive powder 3 is 8.2 wt %;
[0108] (6) A modified topcoat layer slurry is coated on the adhesive layer, and after curing, a topcoat layer of a high-release anion synthetic leather with a thickness of 0.03 mm is formed, wherein the content of the anion-releasing powder 3 in the topcoat layer is 11.7 wt %, and the content of the conductive powder 4 is 12.1 wt %.
[0109] The content of negative ion releasing powder in the finally prepared high-release negative ion synthetic leather is 20.2wt%, and the negative ion release concentration per second in the high-release negative ion synthetic leather is 1557ions / cm 3 .
[0110] Example 3
[0111] A method for preparing high-release negative ion synthetic leather, the specific steps are as follows:
[0112] (1) Preparation of polyurethane modified slurry for base fabric layer: The conductive powder 4 and the negative ion releasing powder 2 are first mixed with a solvent to form a slurry, and then stirred and mixed with the polyurethane resin slurry 1 to prepare a polyurethane modified slurry for the base fabric layer with a viscosity of 30000 CPS;
[0113] Among them, the content of the negative ion releasing powder 2 is 10.2wt%, the content of the conductive powder 4 is 1wt%, and the total solid content of the polyurethane modified slurry of the base fabric layer is 32wt%;
[0114] (2) Modified adhesive layer slurry preparation: The conductive powder 3 and the negative ion releasing powder 1 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 2 to prepare a modified adhesive layer slurry with a viscosity of 80,000 CPS;
[0115] Among them, the content of the negative ion releasing powder 1 is 9.3wt%, the content of the conductive powder 3 is 2.3wt%, and the total solid content of the modified bonding layer slurry is 46.4wt%;
[0116] (3) Preparation of modified topcoat layer slurry: The conductive powder 4 and the negative ion releasing powder 2 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 3 to prepare a modified topcoat layer slurry with a viscosity of 2000 CPS;
[0117] Among them, the content of the negative ion releasing powder 2 is 3.8wt%, the content of the conductive powder 4 is 2.5wt%, and the total solid content of the modified topcoat layer slurry is 27.5wt%;
[0118] (4) using a base fabric layer polyurethane slurry to impregnate a non-woven fabric, and after coagulation and water washing, a sea-island fiber base fabric layer with a thickness of 0.6 mm is prepared, and then a microfiber base fabric layer is obtained after weight reduction, wherein the content of the negative ion releasing powder 2 in the microfiber base fabric layer is 21.9wt%, and the content of the conductive powder 4 is 2.2wt%;
[0119] (5) coating the modified adhesive layer slurry on the microfiber-based fabric layer, and forming an adhesive layer of a high-release anion synthetic leather with a thickness of 0.07 mm after curing, wherein the content of the anion-releasing powder 1 in the adhesive layer is 20 wt %, and the content of the conductive powder 3 is 5.0 wt %;
[0120] (6) A modified topcoat layer slurry is coated on the adhesive layer, and after curing, a topcoat layer of a high-release anion synthetic leather with a thickness of 0.03 mm is formed, wherein the content of the anion-releasing powder 2 in the topcoat layer is 13.8 wt %, and the content of the conductive powder 4 is 9.1 wt %.
[0121] The content of negative ion releasing powder in the finally prepared high-release negative ion synthetic leather is 15wt%, and the negative ion release concentration per second in the high-release negative ion synthetic leather is 1239ions / cm3 .
[0122] Example 4
[0123] A method for preparing high-release negative ion synthetic leather, the specific steps are as follows:
[0124] (1) Preparation of polyurethane modified slurry for base fabric layer: The conductive powder 1 and the negative ion releasing powder 2 are first mixed with a solvent to form a slurry, and then stirred and mixed with the polyurethane resin slurry 1 to prepare a polyurethane modified slurry for the base fabric layer with a viscosity of 40000 CPS;
[0125] Among them, the content of the negative ion releasing powder 2 is 8.8wt%, the content of the conductive powder 1 is 2.5wt%, and the total solid content of the polyurethane modified slurry of the base fabric layer is 33.5wt%;
[0126] (2) Modified adhesive layer slurry preparation: The conductive powder 1 and the negative ion releasing powder 2 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 2 to prepare a modified adhesive layer slurry with a viscosity of 80,000 CPS;
[0127] Among them, the content of the negative ion releasing powder 2 is 6.2wt%, the content of the conductive powder 1 is 3.1wt%, and the total solid content of the modified bonding layer slurry is 44.5wt%;
[0128] (3) Preparation of modified topcoat layer slurry: The conductive powder 1 and the negative ion releasing powder 3 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 3 to prepare a modified topcoat layer slurry with a viscosity of 3000 CPS;
[0129] Among them, the content of the negative ion releasing powder 3 is 2.4wt%, the content of the conductive powder 1 is 2.5wt%, and the total solid content of the modified topcoat layer slurry is 27wt%;
[0130] (4) using the polyurethane slurry of the base fabric layer to impregnate the non-woven fabric, and after coagulation and water washing, a sea-island fiber base fabric layer with a thickness of 1.2 mm is prepared, and then after reduction, an ultra-fine fiber base fabric layer is obtained, wherein the content of the negative ion releasing powder 2 in the ultra-fine fiber base fabric layer is 18 wt %, and the content of the conductive powder 1 is 5.1 wt %;
[0131] (5) coating the modified adhesive layer slurry on the microfiber-based fabric layer, and forming an adhesive layer of a high-release anion synthetic leather with a thickness of 0.07 mm after curing, wherein the content of the anion-releasing powder 2 in the adhesive layer is 13.9 wt %, and the content of the conductive powder 1 is 7 wt %;
[0132] (6) A modified topcoat layer slurry is coated on the adhesive layer, and after curing, a topcoat layer of a high-release anion synthetic leather with a thickness of 0.05 mm is formed, wherein the content of the anion-releasing powder 3 in the topcoat layer is 8.9 wt %, and the content of the conductive powder 1 is 9.3 wt %.
[0133] The content of negative ion releasing powder in the finally prepared high-release negative ion synthetic leather is 23wt%, and the negative ion release concentration per second in the high-release negative ion synthetic leather is 1835ions / cm 3 .
[0134] Example 5
[0135] A method for preparing high-release negative ion synthetic leather, the specific steps are as follows:
[0136] (1) Preparation of polyurethane modified slurry for base fabric layer: The conductive powder 1 and the negative ion releasing powder 1 are first mixed with a solvent to prepare a slurry, and then stirred and mixed with the polyurethane resin slurry 1 to prepare a polyurethane modified slurry for the base fabric layer with a viscosity of 40000 CPS;
[0137] Among them, the content of negative ion releasing powder 1 is 8.6wt%, the content of conductive powder 1 is 1wt%, and the total solid content of the polyurethane modified slurry of the base fabric layer is 32.1wt%;
[0138] (2) Modified adhesive layer slurry preparation: The conductive powder 1 and the negative ion releasing powder 2 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 2 to prepare a modified adhesive layer slurry with a viscosity of 70,000 CPS;
[0139] Among them, the content of the negative ion releasing powder 2 is 6.1wt%, the content of the conductive powder 1 is 3wt%, and the total solid content of the modified bonding layer slurry is 43.3wt%;
[0140] (3) Preparation of modified topcoat layer slurry: The conductive powder 2 and the negative ion releasing powder 3 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 3 to prepare a modified topcoat layer slurry with a viscosity of 2000 CPS;
[0141] Among them, the content of the negative ion releasing powder 3 is 2.4wt%, the content of the conductive powder 2 is 3.2wt%, and the total solid content of the modified topcoat layer slurry is 26.7wt%;
[0142] (4) using the polyurethane slurry of the base fabric layer to impregnate the non-woven fabric, and after coagulation and water washing, a sea-island fiber base fabric layer with a thickness of 1.2 mm is prepared, and then after reduction, an ultra-fine fiber base fabric layer is obtained, wherein the content of the negative ion releasing powder 1 in the ultra-fine fiber base fabric layer is 18 wt %, and the content of the conductive powder 1 is 2.1 wt %;
[0143] (5) coating a modified adhesive layer slurry on the microfiber-based fabric layer, and after curing, forming an adhesive layer of a high-release anion synthetic leather with a thickness of 0.1 mm, wherein the content of the anion-releasing powder 2 in the adhesive layer is 14.1 wt %, and the content of the conductive powder 1 is 6.9 wt %;
[0144] (6) A modified topcoat slurry is coated on the adhesive layer, and after curing, a topcoat layer of a high-release anion synthetic leather with a thickness of 0.03 mm is formed, wherein the content of the anion-releasing powder 3 in the topcoat layer is 9 wt %, and the content of the conductive powder 2 is 12 wt %.
[0145] The content of negative ion releasing powder in the finally prepared high-release negative ion synthetic leather is 23.3wt%, and the negative ion release concentration per second in the high-release negative ion synthetic leather is 1911ions / cm 3 .
[0146] Example 6
[0147] A method for preparing high-release negative ion synthetic leather, the specific steps are as follows:
[0148] (1) Preparation of polyurethane modified slurry for base fabric layer: The conductive powder 1 and the negative ion releasing powder 1 are first mixed with a solvent to prepare a slurry, and then stirred and mixed with the polyurethane resin slurry 1 to prepare a polyurethane modified slurry for the base fabric layer with a viscosity of 40000 CPS;
[0149] Among them, the content of negative ion releasing powder 1 is 11.4wt%, the content of conductive powder 1 is 1wt%, and the total solid content of the polyurethane modified slurry of the base fabric layer is 34.4wt%;
[0150] (2) Modified adhesive layer slurry preparation: The conductive powder 1 and the negative ion releasing powder 1 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 2 to prepare a modified adhesive layer slurry with a viscosity of 90000 CPS;
[0151] Among them, the content of negative ion releasing powder 1 is 9.6wt%, the content of conductive powder 1 is 2.4wt%, and the total solid content of the modified bonding layer slurry is 48.1wt%;
[0152] (3) Preparation of modified topcoat layer slurry: The conductive powder 2 and the negative ion releasing powder 2 are first mixed with a solvent to prepare a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry 3 to prepare a modified topcoat layer slurry with a viscosity of 2000 CPS;
[0153] Among them, the content of the negative ion releasing powder 2 is 4.8wt%, the content of the conductive powder 2 is 2.2wt%, and the total solid content of the modified topcoat layer slurry is 28.2wt%;
[0154] (4) using the polyurethane slurry of the base fabric layer to impregnate the non-woven fabric, and after coagulation and water washing, a sea-island fiber base fabric layer with a thickness of 1.5 mm is prepared, and then after reduction, an ultra-fine fiber base fabric layer is obtained, wherein the content of the negative ion releasing powder 1 in the ultra-fine fiber base fabric layer is 22.9 wt %, and the content of the conductive powder 1 is 2 wt %;
[0155] (5) coating a modified adhesive layer slurry on the microfiber-based fabric layer, and forming an adhesive layer of a high-release anion synthetic leather with a thickness of 0.07 mm after curing, wherein the content of the anion-releasing powder 1 in the adhesive layer is 20 wt %, and the content of the conductive powder 1 is 5 wt %;
[0156] (6) A modified topcoat layer slurry is coated on the adhesive layer, and after curing, a topcoat layer of a high-release anion synthetic leather with a thickness of 0.03 mm is formed, wherein the content of the anion-releasing powder 2 in the topcoat layer is 17 wt %, and the content of the conductive powder 2 is 7.8 wt %.
[0157] The content of negative ion releasing powder in the finally prepared high-release negative ion synthetic leather is 36.3wt%, and the negative ion release concentration per second in the high-release negative ion synthetic leather is 2743ions / cm 3 .
Claims
1. A high-release negative ion synthetic leather, comprising a base fabric layer, an adhesive layer and a topcoat layer, characterized in that: Negative ion releasing powder and conductive powder are added to the base fabric layer, adhesive layer and topcoat layer at the same time; The content of negative ion releasing powder in the base fabric layer, the bonding layer and the topcoat layer decreases in sequence, and the content of conductive powder increases in sequence.
2. The high-release negative ion synthetic leather according to claim 1, characterized in that: The increase rate is ≥1%, and the decrease rate is ≥1%.
3. The high-release negative ion synthetic leather according to claim 1, characterized in that: The content of negative ion releasing powder in the high-release negative ion synthetic leather is more than 15wt%.
4. The high-release negative ion synthetic leather according to claim 3, characterized in that: The thickness of the base fabric layer is 0.6-1.5 mm; the total content of the negative ion releasing powder and the conductive powder in the base fabric layer is ≤25wt%, and the content of the conductive powder is ≥2wt%.
5. The high-release negative ion synthetic leather according to claim 4, characterized in that: The thickness of the bonding layer is 0.05-0.1 mm; the total content of the negative ion releasing powder and the conductive powder in the bonding layer is less than or equal to 25 wt%.
6. The high-release negative ion synthetic leather according to claim 5, characterized in that: The thickness of the topcoat layer is 0.02-0.05 mm; the total content of the negative ion releasing powder and the conductive powder in the topcoat layer is ≤25wt%.
7. The high-release negative ion synthetic leather according to claim 1, characterized in that: Negative ion release powder’s negative ion release concentration per second is ≥1000ions / cm 3 The resistivity of conductive powder is ≤1*10 3 Ω·cm.
8. The method for preparing a high-release anion synthetic leather according to any one of claims 1 to 7, characterized in that The steps include: (1) Configuration of polyurethane modified slurry of base fabric layer: The polyurethane modified slurry of base fabric layer is a slurry containing conductive powder, negative ion releasing powder and polyurethane resin; (2) Modified adhesive layer slurry configuration: The modified adhesive layer slurry is a slurry containing conductive powder, negative ion releasing powder and polyurethane resin; (3) Modified topcoat layer slurry configuration: The modified bonding layer slurry is a slurry containing conductive powder, negative ion releasing powder and polyurethane resin; (4) using a base fabric layer polyurethane modified slurry to impregnate a non-woven fabric to form a base fabric layer; (5) coating the modified adhesive layer slurry on the base fabric layer, and forming an adhesive layer of the high-release anion synthetic leather after curing; (6) coating a modified topcoat slurry on the adhesive layer, and forming a topcoat layer of a high-release anion synthetic leather after curing.
9. The method for preparing a high-release anion synthetic leather according to claim 8, characterized in that: When the polyurethane modified slurry of the base fabric layer, the modified adhesive layer slurry and the modified topcoat layer slurry are configured, the negative ion releasing powder and the conductive powder are first mixed with the solvent to form a slurry, and the slurry is then stirred and mixed with the polyurethane resin slurry.
10. The method for preparing a high-release anion synthetic leather according to claim 9, characterized in that: The viscosity of the polyurethane modified slurry of the base fabric layer is 30000~50000CPS; The viscosity of the modified bonding layer slurry is 70000~90000CPS; The viscosity of the modified topcoat layer slurry is 1000-3000 CPS.
Citation Information
Patent Citations
Method for preparing non-woven fabric with strong function of emitting negative ions
CN108049032A